Socialno delo v interdisciplinarnih raziskavah - Mali, Jana (Socialno delo, 2019)
Researching the social dimensions of dementia has had an international tradition of over thirty years, but has been present in Slovenia only in recent two decades. Nevertheless, we have been following research trends from the very beginning, since we are introducing a user perspective into research, which is the central conceptual guide of social work. For the past four years, we have focused our research on dementia in interdisciplinary projects. The purpose and objectives of the three interdisciplinary research studies and their results are outlined in the paper. We supplemented social work knowledge with various sciences, i.e. the technical sciences, humanities and social sciences. On the one hand, the knowledge and concepts of social work with people with dementia in these studies were tested and supplemented, but on the other hand, we maintained a users' perspective with the advocacy attitude towards people with dementia and tested its use in the participating sciences. Interdisciplinary research into dementia has proven to be an area of new knowledge for dealing with, and for, people with dementia
Keywords: bivalno okolje; demenca; destigmatizacija; gerontologija; oskrba; oskrbovalci; socialno delo; uporabniki